2016
DOI: 10.1515/pjvs-2016-0081
|View full text |Cite
|
Sign up to set email alerts
|

7S Fragment of Type IV Collagen as a Serum Marker of Canine Liver Fibrosis

Abstract: The aim of this study was to assess whether the serum levels of the 7S fragment of type IV collagen may aid in diagnosing liver fibrosis in dogs. The study was carried out on 20 dogs with liver disease. Serum levels of the 7S fragment of type IV collagen were measured in all dogs. The analysis showed that healthy dogs and dogs with type 1, 2 and 3 liver fibrosis had low serum concentrations of the 7S fragment of type IV collagen compared to dogs with type 4 liver fibrosis. The study revealed that the assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Our study, as well as previously reported studies of liver biomarkers in dogs have enrolled relatively few dogs with cirrhosis. This is an important limitation because many biomarker studies in humans focus on distinguishing cirrhotic from non‐cirrhotic patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our study, as well as previously reported studies of liver biomarkers in dogs have enrolled relatively few dogs with cirrhosis. This is an important limitation because many biomarker studies in humans focus on distinguishing cirrhotic from non‐cirrhotic patients.…”
Section: Discussionmentioning
confidence: 85%
“…In another study, serum hyaluronic acid concentrations were distinctly higher in dogs with stage 4 fibrosis, although statistical comparisons were not made . The same research group also reported significantly higher serum concentrations of type III procollagen aminopeptide (PIIINP) and a fragment of type IV collagen (PIVNP) in dogs with advanced liver fibrosis . However, these findings for hyaluronic acid and PIIINP could not be replicated in another study .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A number of molecules including collagen types I [87], III [88], and IV [89] are present in increased amounts in fibrotic livers. For example, the amount of type I collagen in fibrotic livers is increased from 36% to 53% compared to the normal liver [90]. The results of the studies using molecular imaging are exciting and the details are elaborated below.…”
Section: Evaluation Of Liver Fibrosis Using Molecular Imagingmentioning
confidence: 99%
“…Serum hyaluronic acid concentration is increased in dogs with hepatic disease, especially cirrhosis, and therefore holds some promise as a biomarker . Serum concentrations of TGFβ‐1, the 7S fragment of type IV collagen, and procollagen type III N‐terminal peptide also have been found to be increased in dogs with hepatic fibrosis. Another study did not find a positive correlation between hepatic fibrosis and serum concentrations of hyaluronic acid, procollagen type III N‐terminal peptide, or TIMP‐1 .…”
Section: Diagnosis Of Hepatic Fibrosismentioning
confidence: 99%